Analysis of the Definitions of the Education Models of the Universties Member of the Central American University Superior Council (CSUCA) (Revista Electrónica Calidad en la Educación Superior, 2019)
As part of a research on the current status of distance education and the use of information and communication technologies (ICT) in the member universities of CSUCA, a specific objective is identified to identify the concepts of various modalities of university education, according to the existing regulation of those universities. This research was carried out during 2017 and 2018, from a qualitative approach with a narrative design. We used a questionnaire validated by international experts with open questions applied to officials appointed by the Vice-Chancellors or Academic Deans of the member Universities of CSUCA. We get to know the concordance in the mentions of definition and characterization of open, traditional and virtual education. However, ambiguous expressions are detected in the description of the blended and distance model. Aspects that indicate the need for homologation of the different definitions of the university educational models used by the member universities of the CSUCA.
Keywords: : Distance education; open education; traditional education; blended learning; virtual education; CSUCA.